Habitat characteristic and density of larva Aedes albopictus in Curug, Tangerang District, Banten Province, Indonesia 2018 (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Yuliani DM, Hadi UK, Soviana S, Retnani EB. 2021. Habitat characteristic and density of larva Aedes albopictus in Curug, Tangerang District, Banten Province, Indonesia 2018. Biodiversitas 22: 5350-5357. Aedes albopictus, an aggressive, strong, anthropophilic, exophilic, and exophagic mosquito, was an important vector of dengue fever, chikungunya and yellow fever; it became public health problem all over the world. Larvae of Ae. albopictus live in water-filled various types of containers. The study aimed to measure habitat characteristics and the density of larvae of Ae. albopictus in Curug Subdistrict, Tangerang District. This research was conducted in seven endemic villages of Curug Subdistrict, from January to July 2018. Mosquito larvae were collected in 100 houses in every village, the total samples were 700 houses, and observed all outdoor water containers. In this study, 2990 containers consisted of 1545 (51.67%) controllable containers and 1445 (48.33%) disposable containers. Containers positive for Ae. albopictus were 1320 containers from 597 (45.23%) controllable containers and 723 (54.77%%) disposable containers. The larval density indices were 44.96% (Container Index, CI) and 188.57% (Breteau Index, BI). The analysis Maya index in seven villages in Curug Subdistrict showed that 72.57% belonged to the moderate category, so that the area had the potential as breeding sites of Ae. albopictus. Habitat characteristics of Ae. albopictus in Curug Subdistrict was mostly in disposable containers outside the house.
Keywords: Aedes albopictus; containers; larvae; habitat; outdoor